Propolis of Trigona spp. Protects Mucosa from Aspirin-Induced Gastric Mucosal Damage in Rats - Achadiyani Achadiyani; Anindita Laksmi; Dolvy Girawan (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Helicobacter pylori and non-steroid anti-inflammatory drugs are the major causes of peptic ulcer in the world. Indonesian native stingless bee species, Trigona spp., produces propolis that might be effective to protect mucosal damage. The aim of the study was to determine the protective effect of Trigona spp. propolis on aspirin-induced gastric mucosal damage in rats.Methods: This experimental study was conducted from September–November 2013 at Animal Laboratory of Department of Pharmacology and Therapy Faculty of Medicine Universitas Padjadjaran. Healthy male Wistar rats (n=24) aged 2–3 months old and weighed 200–250 grams were randomly divided into three groups. The first group was control negative, the second group was given 100 mg/kg body weight of aspirin, and the third group was given 200 mg/kg body weight of Trigona spp. propolis, one hour before administration of 100 mg/kg body weight of aspirin. After two weeks of treatment, rats were sacrificed by laparotomy to obtain gastric tissues, followed by processing for the paraffin section for histopathological analysis. The grade of gastric mucosal damage was determined under a light microscope. Data were then compared between groups using the Mann-Whitney test.Results: Oral administration of aspirin-induced gastric mucosal damage ranging from grade 0 to grade IV; whereas administration of propolis showed a reduction of gastric mucosal damage’s grade when compared to the aspirin group (p<0.05).Conclusions: Trigona spp. propolis has a protective effect on aspirin-induced gastric mucosal damage. Further study is encouraged to study an optimal dose of aspirin after propolis administration.